Oestrone-targeted liposomes for mitoxantrone delivery via oestrogen receptor – synthesis, physicochemical characterization and in-vitro evaluation. (26th April 2017) - Hao, Qiang; Xu, Guoxing; Yang, Yue; Sun, Yuxin; Cong, Dengli; Li, Hongrui; Liu, Xin; Wang, Zeng; Zhang, Zheng; Chen, Jinglin; Li, Yao; Luan, Xue; et al.
Abstract: Objectives: Targeted delivery of mitoxantrone (MTO, an anthraquinone drug with high antitumour effect) may be achieved using a novel nanoparticulate delivery system via binding the oestrogen receptor (ER, highly expressed in a variety of human tumours). Methods: A novel liposomal nanoparticle (NP) was developed using a conjugate derived from 1, 2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[amino (polyethylene glycol)-2000] (DSPE-PEG2000 -NH2 ) and oestrone (ES, is known to bind the ER) to produce an ES-targeted PEGylated liposome (ES-SSL). The resulting targeted NP was loaded with MTO to produce a targeted liposome-MTO formulation (ES-SSL-MTO). Key findings: The targeted formulation (~140 nm, 1.5 mV) achieved over 95% drug encapsulation efficiency and a favourable stability at 4, 25 and 37 °C up to 48 h. The flow cytometric data indicated that cellular uptake of ES-SSL into human leukaemia HL-60 cells was mediated via binding the oestrogen receptor. In addition, the ES-SSL-MTO significantly reduced the growth of HL-60 cells. Conclusions: Our results provide a proof of principle that ES-modified PEGylated liposomes can target the ER, thereby potentially improving the therapeutic benefits in ER-overexpressed tumours.